Cultivating Religious Attitudes Among Fifth-Grade Students through Inspirational Stories in Indonesian Language Learning - Nur Afifah Rohmah; Heny Friantary; Andre Taulani (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study aims to describe the cultivation of religious attitudes among fifth-grade students through inspirational stories in Indonesian language learning at MIS Al-Islam Bengkulu. This study employed a qualitative descriptive approach. The participants consisted of a fifth-grade teacher and selected students chosen through purposive sampling. Data were collected through observation, interviews, and documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation, technique triangulation, and member checking. The findings showed that the cultivation of religious attitudes was carried out through three stages: planning, implementation, and evaluation. During the planning stage, the teacher integrated religious values into lesson plans and selected inspirational stories containing Islamic messages and moral lessons. During implementation, students participated in reading, discussion, and reflection activities that encouraged them to understand and practice religious values in their daily lives. Evaluation was conducted through observation of students’ attitudes and learning participation. The findings indicate that inspirational stories are effective in fostering religious attitudes because they present values in a meaningful and contextual manner. The stories helped students develop attitudes such as honesty, gratitude, responsibility, respect for others, and obedience to religious teachings.